The Influence of Hedonic Motivation and Brand Love on Impulsive Buying of Muslim Fashion Products with Positive Emotion as an Intervening Variable - Salsabila, Annisa Zahra; Sholahuddin, Muhammad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study investigates the influence of hedonic motivation and brand love on the impulsive buying behavior of Muslim fashion products, with positive emotion as an intervening variable. The research focuses on millennial and Gen Z women as the target respondents. The data was collected using an online questionnaire distributed to 150 female respondents aged between 18 and 35 years old. The results of the analysis, conducted using the Structural Equation Modeling (SEM) technique with Smarts software, revealed several important findings. The results indicate that hedonic motivation has a significant positive effect on impulsive buying behavior of Muslim fashion products (t-statistic = 3.082, P < 0.05), supporting H1. Similarly, brand love also shows a significant positive influence on impulsive buying behavior (t-statistic = 2.234, P < 0.05), supporting H2. However, the relationship between positive emotion and impulsive buying was found to be non-significant (t-statistic = 1.091, P > 0.05), rejecting H3. Furthermore, hedonic motivation was found to have a positive effect on positive emotion (t-statistic = 2.644, P < 0.05), supporting H4. Brand love also has a positive impact on positive emotion (t-statistic = 5.179, P < 0.05), supporting H5. These findings provide insightful information for marketers and businesses to understand the purchasing behavior of millennial and Gen Z women when it comes to Muslim fashion products. The study suggests that while hedonic motivation and brand love directly influence impulsive buying behavior, positive emotion does not fully mediate these relationships. Future research could explore additional variables to enhance the understanding of impulsive buying behavior in the context of Muslim fashion products.